2022
DOI: 10.1101/2022.07.11.499392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrogen stable isotope probing of lipids demonstrates slow rates of microbial growth in soil

Abstract: The rate at which microorganisms grow and reproduce is fundamental to our understanding of microbial physiology and ecology. While soil microbiologists routinely quantify soil microbial biomass levels and the growth rates of individual taxa in culture, there is a limited understanding of how quickly microbes actually grow in soil. For this work, we posed the simple question: what are the growth rates of soil microorganisms? In this study, we measure these rates in three distinct soil environments using hydroge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…Therefore, to accurately estimate microbial fatty acid production the physiological parameter ‘water hydrogen assimilation constant (a w )’ should be applied ( 74 , 75 ), obtained from the regression of the 2 H isotopic composition of fatty acids and water source. In a recent survey it was demonstrated that a w can range from values close to 0.1 up to values close to 1 ( 76 ). In complex communities, such as soil, the assimilation constant is difficult to estimate, but assuming all microbes are heterotrophs, this value is on average 0.71 ( 35 ), which we also applied in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to accurately estimate microbial fatty acid production the physiological parameter ‘water hydrogen assimilation constant (a w )’ should be applied ( 74 , 75 ), obtained from the regression of the 2 H isotopic composition of fatty acids and water source. In a recent survey it was demonstrated that a w can range from values close to 0.1 up to values close to 1 ( 76 ). In complex communities, such as soil, the assimilation constant is difficult to estimate, but assuming all microbes are heterotrophs, this value is on average 0.71 ( 35 ), which we also applied in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Deuterium ( 2 H) incorporation into fatty acids can serve as an alternative SIP approach to measure microbial growth, as all microorganisms synthesize lipids and fatty acids to build and maintain cell membranes regardless of their metabolic activity and cell cycle stage. 2 H-labelling has been used in single cell studies ( 33 ), pure cultures ( 34 ) and soil microbial communities ( 35 ). Lipids likely require less investment into repair mechanisms compared to nucleic acids or proteins, which can be resynthesized during repair and cellular maintenance potentially affecting growth rates calculation ( 35 , 36 ), and provide a precise measure of microbial membrane production rates and cell growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although long‐term in vitro microbial evolution experiments have shown strong evidence for adaptation (Lenski, 2017; Rainey & Travisano, 1998; Rodríguez‐Verdugo, 2021; Travisano & Lenski, 1996), it is unclear if these observations extend to natural systems (Koskella & Vos, 2015). In the few examples investigating the impact of evolution within natural communities, it appears that slow generation times (Caro et al, 2022) combined with high spatial heterogeneity may limit detection of genome evolution and result in different evolutionary dynamics than those observed in laboratory environments (Chase et al, 2021). Resolving the feedbacks between ecological and evolutionary processes will be essential for improving model predictions of biogeochemical functions, and might contradict the current belief that biodiversity inhibits evolutionary responses to changing environments (de Mazancourt et al, 2008; Johansson, 2008; Loeuille & Leibold, 2008).…”
Section: What Ecological and Evolutionary Processes Drive Functional ...mentioning
confidence: 99%
“…A novel approach to modeling community-wide temperature responses of soil bacteria using thermal niche theory 141 5 (Nottingham et al, 2021). Current estimates of turnover times for bacterial community biomass vary largely from 2 to 169 days (Caro et al, 2022). The large deviation in growth rates might be explained by other environmental factors such as soil moisture, plant-soil interactions, pH, substrate quantity and quality (Rousk and Bååth, 2011), which means that implementing growth rates into our model would like require more environmental data about the soils.…”
Section: More Realistic Modellingmentioning
confidence: 99%